2014
DOI: 10.7554/elife.01724
|View full text |Cite
|
Sign up to set email alerts
|

The Kinesin-12 Kif15 is a processive track-switching tetramer

Abstract: Kinesin-12 motors are a little studied branch of the kinesin superfamily with the human protein (Kif15) implicated in spindle mechanics and chromosome movement. In this study, we reconstitute full-length hKif15 and its microtubule-targeting factor hTpx2 in vitro to gain insight into the motors mode of operation. We reveal that hKif15 is a plus-end-directed processive homotetramer that can step against loads of up to 3.5 pN. We further show that hKif15 is the first kinesin that effectively switches microtubule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
106
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(116 citation statements)
references
References 32 publications
8
106
2
Order By: Relevance
“…We previously reported that single hKif15-eGFP homotetramers moving on stabilized microtubules dwell for extended periods of time at the microtubule plus-end (12). This observation prompted us to investigate whether such behavior also occurs on dynamic microtubules and whether it influences their plus-end dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that single hKif15-eGFP homotetramers moving on stabilized microtubules dwell for extended periods of time at the microtubule plus-end (12). This observation prompted us to investigate whether such behavior also occurs on dynamic microtubules and whether it influences their plus-end dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…These motors are highly processive, capable of switching tracks at microtubule intersections, and can step against loads of up to 3.5 pN (12). Kif15 tetramers can also mediate the cross-linking of two microtubules, but give rise to very little microtubule sliding, except for episodes of short duration transport of short microtubules (12). A second study recently reported that a dimeric Kif15 missing the carboxyl-terminal half of the protein is also able to drive microtubule transport (13).…”
mentioning
confidence: 99%
See 3 more Smart Citations